Association between asthma control and healthcare costs: Results from a German linked data study. (February 2023) - Wilke, Thomas; Timmermann, Hartmut; Mueller, Sabrina; Hardtstock, Fraence; Unmuessig, Victoria; Welte, Robert R; Maywald, Ulf
Background : This study aimed to evaluate differences in healthcare resource utilization and cost among patients with controlled and uncontrolled asthma. Methods : Claims data from a German sickness fund was linked to patient survey data. Outpatient physicians enrolled patients and assessed asthma control using the ACT TM questionnaire. All-cause and asthma-specific healthcare resource use (HCRU)/costs were compared descriptively and based on multivariable models using a continuous ACT TM score. Results : Overall, 492 asthma patients were included (mean age: 53.8, 73.8% female). The mean/median ACT TM score was 19.9/20.7, with 183 patients (37.2%) classified as having uncontrolled asthma (mean ACT TM score<20) Patients with uncontrolled asthma had significantly more hospitalizations ( p = .035) and medication prescriptions ( p < .001), which resulted in higher total healthcare costs for asthma-related (€1785 vs. €1615; p = .004) and all-cause care (€4695 vs. €4117; p = .009). While controlling for baseline characteristics, multivariable models confirmed a negative association between asthma control and total all-cause healthcare costs ( p = .008), total asthma-related costs ( p = .008), and costs of medication prescriptions ( p = .001). However, no significant association was found for all-cause ( p = .062) and asthma-related hospitalization costs ( p = .576). Conclusion : Considering continuous patient care, improving asthma control is not only desirable from a clinical perspective, but could also be an effective approach to reduce asthma-related HCRU and cost burden.